Success and failure of reindeer herding in Greenland - Cuyler, Christine (Rangifer, 1999)
Animal husbandry is a recent innovation in Greenland, specifically reindeer husbandry is less than 50 years old. Reindeer husbandry was first established in mid-west Greenland and later in southern Greenland. The Greenland hunter tradition and culture is, however, still dominant in many communities. During the 1980s and 1990s, the incompatibility of these two traditions resulted in the failure of reindeer husbandry in mid-west Greenland. There were neither herding nor seasonal herd movements. Animals remained year round on the winter range, which was destroyed as lichens were trampled every summer. Without seasonal herd movements both sustainable range use and control of the herd were lost. Today, there are just two semi-domestic reindeer herds left, and both are in southern Greenland. One herd is commercially successful, and the other is under development. In mid-west Greenland, semi-domestic reindeer husbandry officially ended in 1998, and a hunt was initiated to remove the remaining population. Possibly, by the year 2000 any animals left in this region will be considered wild caribou.